ENSO regimes: reinterpreting the canonical and Modoki El Niño - Takahashi, Ken (2011)
We propose that the first two empirical orthogonal function (EOF) modes of tropical Pacific sea surface temperature (SST) anomalies do not describe different phenomena (i.e., El Niño‐Southern Oscillation (ENSO) and “El Niño Modoki”) but rather the nonlinear evolution of ENSO. We introduce two new uncorrelated indices (E and C), based on the leading EOFs, that respectively account for extreme warm events in the eastern and cold/moderate warm events in the central equatorial Pacific, corresponding to regimes with different evolution. Recent trends in ENSO can be described as an increase in the central Pacific (C) variability that is associated with stronger cold events, as well as a reduction in the eastern Pacific (E) variability within the cold/moderate warm regime, consistent with model projections. However, little can be said observationally with respect to the extreme warm regime.